Economic development - Todaro, Michael. P. (London, 1997)
This book is designed for use in courses that focus on the economics of development in Africa, Asia, and Latin America, regions often collectively referred to as the Third World. It is structured and written both for students who have had some basic training in economics and for those with little or no formal economics back ground. For both groups, essential principles and concepts of economics that are particularly relevant for understanding development problems are highlighted in boldface and explained at appropriate points throughout the text. They are also defined in a detailed and extensive glossary which includes other terms and concepts that may be unfamiliar to non-economics majors. Thus the book should be of special value in undergraduate development courses that attract students from a variety of disciplines. Yet the material is sufficiently broad in scope and rigorous in coverage to satisfy any undergraduate and some graduate economics requirements in the field of development.
Keywords: Economic development